NHL-ChirEx: An interprofessional cross-border education initiative in the Greater Region with a focus on radiation morbidity and patient safety. Issue 3 (December 2018) - Vogin, Guillaume; Fleckenstein, Jochen; Servotte, Jean-Christophe; Nickers, Philippe; Ebersberger, Anne; Mohammad, Farid; Bragard, Isabelle; Coucke, Philippe; Untereiner, Michel; Peiffert, Didier; Braun, Marc; ,
Abstract: NHL-ChirEx is an interprofessional cross-border education project that addresses the potential excess of radiation induced morbidity throughout the radiation planning and treatment process. NHL-ChirEx is supported by ESTRO and the University of the Greater Region and has been recently approved and funded under INTERREG VA Programme.